Hybrid transaction model for optimizing the distributed power trading market - Qianwen Li; Zhilong Chen; Jialin Min; Mengjie Xu; Yanhong Zhan; Wenyue Zhang; Chuanwang Sun (Humanities & Social Sciences Communications)
Abstract The distributed power (DP) trading market plays a pivotal role in promoting renewable energy and driving the global economy’s low-carbon transition. However, the DP market worldwide is still in its infancy and faces problems such as immature market mechanisms and fluctuating power generation. To address these challenges, this paper introduces an innovative Hybrid Transaction Model (HTM) designed to optimize DP market mechanisms and refine “grid fee” structures. HTM operates through two structured transaction markets: (1) the aggregation transaction market, which manages trades between aggregators and distributed users; (2) the terminal transaction market, which facilitates exchanges between aggregators and industrial and commercial users. Additionally, HTM integrates a shared energy storage market to support expanding energy storage systems. Using China as a case study, this paper examines the barriers to DP trade market development and offers actionable policy implications for the further development of DP markets in China and comparable regions.